Site‐specific monitoring of N‐Glycosylation profiles of a CTLA4‐Fc‐fusion protein from the secretory pathway to the extracellular environment. Issue 7 (14th March 2017) - Bora de Oliveira, Karina; Spencer, David; Barton, Christopher; Agarwal, Nitin
ABSTRACT: Glycosylation often plays a key role in the safety and efficacy of therapeutic proteins to patients, thus underlying the need for consistent control of this important post‐translational modification during biologics production. In this study, we profiled the site‐specific evolution of N‐glycans on a CTLA4‐Fc‐fusion protein, from the intracellular secretory pathway to the conditioned medium (CM) in fed‐batch cell culture. For this, we developed an approach that combined sub‐cellular fractionation with liquid chromatography‐tandem mass spectrometry (LC‐MS/MS) analyses. The study revealed that there was a significant amount of heterogeneity in the glycans displayed amongst the three distinct N‐glycosylation sites. Furthermore, 54–60% of the intracellular protein was characterized by Man8 and Man9 glycans on day 10, when the cell density peaks, indicative of a significant bottleneck between the endoplasmic reticulum (ER) and the cis‐Golgi. At longer culture duration, the accumulation of intracellular protein with bi‐antennary‐fucosylated GlcNAc‐terminated residues identified the formation of another bottleneck in the medial and trans‐Golgi compartments, which subsequently led to a decrease in sialylated species in the secreted protein. Glucose deprivation caused a reduction in the Man8 and Man9 glycans in favor of Man5 glycans and bi‐antennary‐fucosylated GlcNAc‐terminated residues in the organellar pool of the Fc‐fusion protein. However, transient deprivation of glucose did not lead to major differences in the glycan profile of proteins secreted into the CM. The approach developed here allows us to probe the secretory pathway and sheds light on the site‐specific intracellular processing of glycans during fed‐batch cell culture, thus serving as an initial step towards their rational control. Biotechnol. Bioeng. 2017;114: 1550–1560. © 2017 Wiley Periodicals, Inc. Abstract : Glycosylation is an important post‐translational modification that may significantly affect the efficacy and serum half‐life of therapeutic proteins. This article describes an approach that allows monitoring of the glycan profile of a therapeutic CTLA4‐Fc‐fusion protein from the secretory pathway to the extracellular environment during fed‐batch production. The results from this effort provide insight into the intracellular bottlenecks in glycan‐processing during fed‐batch culture, and how these bottlenecks impact the glycan profile of the secreted Fc‐fusion protein.